2011
DOI: 10.1007/s13594-011-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in transcription profiles reflect strain contributions to defined cultures of Lactococcus lactis subsp. cremoris during milk fermentation

Abstract: Cheddar cheese production uses mixed starters composed of Lactococcus lactis subsp. cremoris strains with complementary or competing enzymatic activity. However, strain interactions within the same subspecies are difficult to investigate by conventional microbiological methods. This study uses fluorescent RNA arbitrarily primed PCR (FRAP-PCR) to analyze the association of three L. lactis subsp. cremoris strains (LL074, LL225, and LL390 with proteinase types: PI, PIII, and PI/PIII, respectively) by monitoring w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Milk treatment by carbon dioxide influenced the transcription profiles of the defined culture, while neutralization by agitation was the best procedure compared with NaOH or Na 2 CO 3 for regaining the original transcription profile at neutral pH (Dachet et al 2010(Dachet et al , 2011. In addition, lowering the rennet activity or increasing NaCl concentration greatly affected the transcription profile of the defined mixed culture.…”
Section: Differential Display Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk treatment by carbon dioxide influenced the transcription profiles of the defined culture, while neutralization by agitation was the best procedure compared with NaOH or Na 2 CO 3 for regaining the original transcription profile at neutral pH (Dachet et al 2010(Dachet et al , 2011. In addition, lowering the rennet activity or increasing NaCl concentration greatly affected the transcription profile of the defined mixed culture.…”
Section: Differential Display Techniquesmentioning
confidence: 99%
“…In addition, lowering the rennet activity or increasing NaCl concentration greatly affected the transcription profile of the defined mixed culture. In combination with Förster resonance energy transfer PCR for discriminating individual strains, instability in strain ratios was demonstrated that could be related to the incompatibility of the different proteinase types of the strains (Dachet et al 2011). Thus, FRAP-PCR could be used to screen strain compatibility and mixed culture associations of lactococcal strains, which would be difficult to accomplish by culture-dependent methods.…”
Section: Differential Display Techniquesmentioning
confidence: 99%